2018
DOI: 10.1073/pnas.1800695115
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cells inhibit T cell activation through nitrating LCK in mouse cancers

Abstract: Potent immunosuppressive mechanisms within the tumor microenvironment contribute to the resistance of aggressive human cancers to immune checkpoint blockade (ICB) therapy. One of the main mechanisms for myeloid-derived suppressor cells (MDSCs) to induce T cell tolerance is through secretion of reactive nitrogen species (RNS), which nitrates tyrosine residues in proteins involved in T cell function. However, so far very few nitrated proteins have been identified. Here, using a transgenic mouse model of prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 28 publications
2
87
0
1
Order By: Relevance
“…On the other hand, CD11b + Ly6C int Ly6G + fraction of CD11b + Gr1 + cells with polymorphonuclear morphology did not suppress T cell activation (44). In tumor models, a large proportion of MDSCs have granulocytic morphology and show increased expression of arginase and iNOS (34,45). In future studies, it will be interesting to see if the functional heterogeneity reported by Tam et al (44).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, CD11b + Ly6C int Ly6G + fraction of CD11b + Gr1 + cells with polymorphonuclear morphology did not suppress T cell activation (44). In tumor models, a large proportion of MDSCs have granulocytic morphology and show increased expression of arginase and iNOS (34,45). In future studies, it will be interesting to see if the functional heterogeneity reported by Tam et al (44).…”
Section: Discussionmentioning
confidence: 96%
“…The exact mechanism by which NO selectively downregulates IL-2 secretion is not clear. A recent study has suggested that CD11b + Gr1 + MDSCs produced during cancers might inhibit IL-2 production through nitration of lck (45). IL-2 is known to play a key role in several critical T-cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the spleen of the tumor-bearing mice gradually expanded as the tumor progressed, and flow cytometry analysis revealed a large number of MDSCs in the spleen and blood of 4T1 tumor-bearing mice, especially in those with advanced tumors. Notably, MDSCs can block T-cell activation by nitrating lymphocyte-specific protein tyrosine kinase, leading to reduced IL-2 production and proliferation 47 and inhibit antigen-specific T cell responses in peripheral lymphoid organs. 21,22 Moreover, a large number of MDSCs exist in the peripheral immune environment of mice at the beginning of the vaccine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…78,79 These cells are able to directly suppress T cell responses and inhibit CD8 T cell infiltration resulting in impaired anti-tumour activity. [78][79][80][81][82] Collectively, this autocrine cascade promotes tumour growth and metastasis. In our model, the blockage of CXCR2 enriched the anti-tumour immune cell compartment and significantly reduced metastatic spread, which highly supports our concept.…”
Section: Discussionmentioning
confidence: 99%